Identification of Mathematical Concepts in Paiton Community Rice Farming Activities - Nanda Aqidah Putri; Shofia Hidayah (Civiliza Publishing, Indonesia., 2026)
School mathematics instruction is often perceived as too abstract and rigid because it is presented separately from the realities of life and the cultural backgrounds of students. This study aims to identify and describe the implementation of geometric concepts, comparisons, number patterns, and social arithmetic at various stages of rice farming activities in the Paiton community, Probolinggo Regency. The method used was a qualitative approach with an ethnographic design through semi-structured interviews with three active farmers in Jabung Candi Village, field observations, and interactive analysis of documentation. The results show that Paiton's agricultural activities are rich in applied mathematical concepts: whole number operations and social arithmetic are used in seed selection and profit-loss calculations; equivalent ratios are applied to fertilizer and pesticide dosages; the geometric structure of spiral curves is formed on tractor plowing tracks; and the Jajar Legowo planting system implements sequences of number patterns. This study concludes that Paiton's rice farming activities validly integrate formal mathematical concepts, thus having strategic implications for their transformation into realistic mathematics learning tools.